ASHRAE design guide for duct systems - Behls, Herman, 1929-2017 (ASHRAE, 2019)
"Provides engineers and other design professionals with the tools and knowledge to design duct systems so that fans are properly sized, minimize the installed cost of the ductwork, minimize system-generated noise, and minimize the fan energy consumption of commercial and industrial duct systems"--